Management of Patients with Guillain-Barré Syndrome and Severe Community-Acquired Pneumonia in the Intensive Care Unit (ICU) - Junaidi , Agus; Budipratama , Dhany (Journal of Society Medicine, 2025)
Introduction: Guillain-Barré Syndrome (GBS) is an immune-mediated polyneuropathy that leads to respiratory failure requiring mechanical ventilation. The neurological deficits in GBS, including airway obstruction, ineffective coughing, and difficulty swallowing, increase pneumonia risk, which worsens patient condition. Community-Acquired Pneumonia (CAP) is a lung infection contracted outside hospitals, and its severity relates to mortality. Appropriate antibiotic therapy is crucial for reducing treatment duration and mortality. Case Report: We report a case of a 20-year-old male who developed respiratory failure due to GBS complicated by severe CAP. The patient was admitted to the ICU, where he received plasmapheresis for GBS treatment, which led to gradual improvement. Due to respiratory failure, the patient required mechanical ventilation. Empirical antibiotic therapy was initiated, considering the severity of CAP and the potential for bacterial resistance. After 13 days of intensive care, the patient was successfully weaned off mechanical ventilation. Conclusion: This case highlights the importance of a timely and comprehensive approach to treating GBS and CAP in the ICU. Plasmapheresis for GBS and appropriate antibiotic therapy for CAP were key in the patient’s recovery. Early intervention and appropriate supportive care, including mechanical ventilation when necessary, are essential for improving patient outcomes. Further studies and refined treatment protocols are needed to optimize care for patients with complex conditions like GBS complicated by CAP.